Runes and words: runic lexicography in context - Jesch, Judith (2013)
The paper begins by noting the lack of a comprehensive dictionary of Scandinavian runic inscriptions, as well as the absence of the runic evidence from most dictionaries of the early Scandinavian languages, and considers possible reasons for this. Runic inscriptions may need a different kind of dictionary, because they require a different kind of reading that takes extra-linguistic as well as linguistic contexts into account (a process that has been called “interdisciplinary semantics”). Using the examples of the words bóndi and þegn in Viking Age inscriptions, the paper shows how the variety of available contexts enables a richer definition of these and other words, which might facilitate a different type of dictionary, based on discursive definitions.